Oral processing behaviours that promote children's energy intake are associated with parent-reported appetitive traits: Results from the GUSTO cohort. (1st July 2018) - Fogel, Anna; Fries, Lisa R.; McCrickerd, Keri; Goh, Ai Ting; Quah, Phaik Ling; Chan, Mei Jun; Toh, Jia Ying; Chong, Yap-Seng; Tan, Kok Hian; Yap, Fabian; Shek, Lynette P.; Meaney, Michael J.; et al.
Abstract: Oral processing behaviours associated with faster eating rates have been consistently linked to increased energy intakes, but little is known about their links to children's appetitive traits. This study used the Child Eating Behaviour Questionnaire (CEBQ) to explore cross-sectional and prospective associations between parent-reported appetitive traits and observed oral processing behaviours. Participants were 195 children from the Growing Up in Singapore Towards healthy Outcomes cohort, who participated in a video-recorded ad libitum lunch at 4.5 (Time 1) and 6 years (Time 2). Their mothers completed the CEBQ around the same time points. Children's bites, chews and swallows were coded, and used to calculate their eating rate, bite size, chews per bite, chew rate, oral exposure time and oral exposure per bite. At Time 1, children with higher scores in slowness in eating had lower eating and chew rates. At Time 2, higher scores for food enjoyment and lower for satiety responsiveness, slowness in eating, and food fussiness were linked with higher eating rates and greater energy intakes (r > 0.16, p < 0.05). Post-hoc analyses revealed that these associations were moderated by BMI and only present among children with higher BMI. Faster eating rates mediated the associations between greater food enjoyment, lower slowness in eating, lower food fussiness and higher intakes of energy. Children with higher slowness in eating scores had lower increases in eating rates over time, and children with higher BMI who had greater food enjoyment and food responsiveness scores had greater increases in eating rates over time. The findings suggest that oral processing behaviours linked with increased obesity risk may be underpinned by appetitive traits and may be one of the behavioural pathways through which these appetitive traits influence energy intakes.